New data on daffodils of the Narcissus nevadensis complex (Amaryllidaceae) in SE Spain: N. nevadensis subsp. herrerae subsp. nov., and N. nevadensis subsp. longispathus comb. nov. - Algarra, Jose A.; Blanca, Gabriel; Cueto, Miguel; Fuentes, Julián (Phytotaxa, 2018)
Narcissus Linnaeus (1753: 289) is a genus widespread in the Mediterranean region and taxonomically very complex, including a broadly variable number of taxa depending on authors. It includes between 26 and 36 species (Webb 1980, Zonneveld 2008), or even up to 110 species recognised in the International Daffodil Register (RHS 2017). In the Iberian Peninsula, 56 taxa (Fernandes 1951) or 33 taxa (Aedo 2013) have been accepted to occur, 10–12 belonging to N. subg. Ajax (Salisb. ex Haworth 1819: 111) Spach (1846: 432) sect. Pseudonarcissus DC. in Redouté (1815: tab. 486). In the south-eastern Iberian Peninsula 16 species (Aedo 2013) to 19 species (Fernandes 1951, Navarro 2011) have been considered, of which one (Aedo 2013) to three (Navarro 2011) correspond to that section, most of them endemic to the area (Bañares et al. 2004, Blanca et al. 1999, 2000, 2001). The Iberian Peninsula is the centre of diversity for N. sect. Pseudonarcissus, with N. nevadensis Pugsley (1933: 62) being proposed as the ancestral species of this group (Fernandes 1951). Recently, after molecular analyses (Zonneveld 2008, Marques et al. 2017), this species has been separated into an independent section: N. sect. Nevadensis Zonneveld (2008: 130).